TEENI-Turboshaft Engine Exhaust Noise Identification - Bennett, Gareth (My University, 2010)
The TEENI project is an FP7 level 1 (Theme 7 ? Transport) 1st Call EU-funded project. It focuses on Helicopter Engine Exhaust Broadband Noise, and tries to identify the origin of this noise from external measurements only. The project was launched on 1 April 2008 and will last 3 years. TEENI, a collaborative project, has EU funding of 3.3M? with 11 partners. Unlike Turbojet engines, Turboshaft engine gases are ejected at low speeds, leading to almost no jet noise. Although the turbines generate high amplitude tonal nose, their high RPM and blade count result in the frequencies being above the audible threshold. However, a previous European project: Friendcopter has demonstrated through flight tests the significance of medium-frequency exhaust engine noise for the Take-Off flight certification condition. The origin and generation mechanisms of this exhaust broadband noise ?Corenoise? ? figure 1, have not yet been fully defined: low frequency content is generally related to combustion phenomena in the literature, but the sources above 1kHz are not understood. Understanding the origin (location and physical mechanisms) of this broadband noise range is the main objective of the TEENI project, with the final industrial goal being to better attenuate this exhaust noise.
TCD-UCD Engineering Design Innovation Research Event
PUBLISHED
Trinity College, Foster Place, Dublin 2
Keywords: Acoustics; Turbomachinery; Turboshaft; Noise Source Identification; FP7; Broadband Noise; Smart & Sustainable Planet